2016
DOI: 10.1007/s11746-016-2840-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fatty Acid Esters of Selected Higher Polyols Over Homogeneous Metallic Catalysts

Abstract: Studies on the synthesis of esters of natural origin fatty acids (oleic acid) and a branched synthetic isostearic acid derived from oleic acid with commercially available selected higher polyols in the presence of homogeneous metallic catalysts have been carried out. The effects of the synthesis temperature, molar ratio and the catalysts amount have also been studied. It was shown that higher fatty acid conversion and selectivity to tri- and tetraesters were obtained for organotin catalyst Fascat 2003, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The amount of basic phosphate was a three-fold molar excess relative to the acid values of the crude esters. This method was considered as the best for purification of crude fatty acid esters of various polyols [28]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of basic phosphate was a three-fold molar excess relative to the acid values of the crude esters. This method was considered as the best for purification of crude fatty acid esters of various polyols [28]. …”
Section: Resultsmentioning
confidence: 99%
“…synthesis of polyesters. Our previous experiments on the esterification reaction of higher fatty acids and polyols conducted over various Ti, Zr and Sn catalysts have shown that homogeneous Sn bis (2-ethylhexanoate) is characterized by the highest activity and selectivity to the desired products [28]. …”
Section: Introductionmentioning
confidence: 99%
“…Plant oil fatty acid esters were synthesised from oleic and ISAs according to previous described method. 44 In the typical synthesis, fatty acid (0.6 mol) and corresponding polyol in the molar ratio COOH: OH 1: 1 were placed in 250-mL four-neck glass reactor equipped with mechanical stirrer and electronic temperature controller. The reactor was equipped with a Claisen condenser and a gas bubbler in order to introduce a weak N 2 flow through the reactor.…”
Section: Figure 1 Fatty Acid Esters Synthesised In This Studymentioning
confidence: 99%
“…The synthesis procedure of plant oil fatty acids of selected polyols (trimethylolpropane and pentaerythritol) has been described in more details in our previous report . In this study, we developed a very effective method of the synthesis of plant oil derived fatty acid esters of higher polyols that have been significantly extended and supplemented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation